Modelling our future population ageing, health, and aged care - Gupta, Anil, statistician; Harding, Ann, 1958- (Elsevier B.V., 2007)
This volume serves to present to interested readers recent developments in microsimulation and public policy. It strings together: selected papers presented at the International Microsimulation Conference on Population Ageing and Health: Modelling Our Future held in Canberra, Australia in December 2003; and recent thinking in the field of microsimulation as reflected in special contributions by some of the leading experts in the field; description of 20 key models relating to fiscal and health human resource issues concerning sustainability of health systems around the globe. The focus of the conference was on practical uses of microsimulation in government policy although theoretical underpinnings also received considerable attention. The volume covers a diversity of subjects: health status; pharmacare and health expenditure issues; financing, caring and health delivery; health human resources; and data challenges. To provide an insight into actual models used around the world, the book also has a section devoted to the challenges associated with building of microsimulation models and their current use in the formulation of public policy. The book presents some innovative analysis on public policy issues contained in some of the conference papers along with the methodological advancements made in the microsimulation field. It contains invaluable information that aims to help shape the current and future public policy debates in this area. The authors are established leaders in the field, and it is international in scope.
A selection of papers from a conference entitled: International Microsimulation Conference on Population Ageing and Health, held Dec. 2003 in Canberra, Australia.
Includes index.
Keywords: Policy sciences -- Computer simulation -- Congresses.; Social sciences -- Computer simulation -- Congresses.; Social sciences -- Forecasting -- Congresses.; Population aging -- Congresses.; Social Science -- Gerontology.; Medical -- Health Care Delivery.; Care of the elderly.; elektronické knihy; electronic books